The vacuolar sulfate transporter PsSULTR4 is a key determinant of seed yield and protein composition in pea - Bachelet, Fanélie; Sanchez, Myriam; Aimé, Delphine; Naudé, Florence; Rossin, Nadia; Ourry, Alain; Deulvot, Chrystel; Le Signor, Christine; Vernoud, Vanessa; Neiers, Fabrice; Wirtz, Markus; Gallardo-Guerrero, Karine (The plant journal, 2024)
Pea is a grain legume crop with a high potential to accelerate the food transition due to its high seed protein content and relatively well-balanced amino acid composition. The critical role of external sulfur (S) supply in determining seed yield and seed quality in pea makes it essential to understand the impact of whole plant S management on the trade-off between these two traits. Here, we investigated the physiological relevance of vacuolar sulfate remobilization by targeting PsSULTR4, the only pea sulfate transporter showing substantial similarity to the vacuolar sulfate exporter AtSULTR4;1. Five mutations in PsSULTR4 were identified by TILLING (Targeting Induced Local Lesions IN Genomes), two of which, a loss of function (W78*) and a missense (E568K), significantly decreased seed yield under S deprivation. We demonstrate that PsSULTR4 triggers S distribution from source tissues, especially lower leaves, to reproductive organs to maintain seed yield under S deficiency. Under sufficient S supply, sultr4 seeds display lower levels of the S-rich storage protein PA1 at maturity. They also overaccumulate sulfate in the endosperm at the onset of seed filling. These findings uncover a role of PsSULTR4 in the remobilization of vacuolar sulfate during embryo development, allowing the efficient synthesis of S-rich proteins. Our study uncovers that PsSULTR4 functions (i) in source tissues to remobilize stored vacuolar sulfate for seed production under low S availability and (ii) in developing seeds well supplied with S to fine-tune sulfate remobilization from the endosperm as a critical control point for storage activities in the embryo.
Online veröffentlicht: 8. August 2024
Gesehen am 08.05.2025